Machine learning and AI with simple Python and Matlab scripts : coursework for non-computing majors - Uyar, M. Ümit (John Wiley and Sons, Inc.; Wiley-IEEE Press, 2025)
A practical guide to AI applications for Simple Python and Matlab scripts Machine Learning and AI with Simple Python and Matlab Scripts: Courseware for Non-computing Majors introduces basic concepts and principles of machine learning and artificial intelligence to help readers develop skills applicable to many popular topics in engineering and science. Step-by-step instructions for simple Python and Matlab scripts mimicking real-life applications will enter the readers into the magical world of AI, without requiring them to have advanced math and computational skills. The book is supported by instructor only lecture slides and sample exams with multiple-choice questions. Machine Learning and AI with Simple Python and Matlab Scripts includes information on: Artificial neural networks applied to real-world problems such as algorithmic trading of financial assets, Alzheimer's disease prognosis Convolution neural networks for speech recognition and optical character recognition Recurrent neural networks for chatbots and natural language translators Typical AI tasks including flight control for autonomous drones, dietary menu planning, and route planning Advanced AI tasks including particle swarm optimization and differential and grammatical evolution as well as the current state of the art in AI tools Machine Learning and AI with Simple Python and Matlab Scripts is an accessible, thorough, and practical learning resource for undergraduate and graduate students in engineering and science programs along with professionals in related industries seeking to expand their skill sets.
Keywords: Machine learning.; elektronické knihy; electronic books